2015
DOI: 10.1016/j.rpped.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Necessidade de tratamento ortodôntico em adolescentes brasileiros: avaliação com base na saúde pública

Abstract: OBJECTIVE: To identify the prevalence and the severity of malocclusions and to analyze factors associated with the need for orthodontic treatment of Brazilian adolescents. METHODS: This exploratory, cross-sectional study was carried out based on secondary data from the national epidemiological survey on oral health in Brazil (2002-2003). Socio-demographic conditions, self-perception, and the existence and degree of malocclusion, using the Dental Aesthetic Index, were evaluated in 16,833 adolescent Brazilians s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
1
4
0
9
Order By: Relevance
“…Ressalta-se que apesar desses estudos terem utilizado o DAI como critério de avaliação, considera-se as diferenças regionais e culturais, assim como o acesso ao tratamento ortodôntico de cada localidade. Considerando os relevantes avanços alcançados no processo de atenção à saúde bucal no Brasil, assim como a possibilidade de acesso ao tratamento ortodôntico em alguns serviços públicos no pais a partir de 2011 5,28 , a prevalência da maloclusão entre crianças brasileiras ainda é bastante elevada. Além disso, possivelmente essa prevalência pode estar relacionada a adoção de comportamentos inadequados que podem agir como fatores de risco para ocorrência desse agravo.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Ressalta-se que apesar desses estudos terem utilizado o DAI como critério de avaliação, considera-se as diferenças regionais e culturais, assim como o acesso ao tratamento ortodôntico de cada localidade. Considerando os relevantes avanços alcançados no processo de atenção à saúde bucal no Brasil, assim como a possibilidade de acesso ao tratamento ortodôntico em alguns serviços públicos no pais a partir de 2011 5,28 , a prevalência da maloclusão entre crianças brasileiras ainda é bastante elevada. Além disso, possivelmente essa prevalência pode estar relacionada a adoção de comportamentos inadequados que podem agir como fatores de risco para ocorrência desse agravo.…”
Section: Discussionunclassified
“…Sua ocorrência tem sido associada a diferentes fatores, tais como, desigualdades sociais 5 , comportamentos 6 e outras doenças bucais, como a cárie dentária 7 . Além disso, a maloclusão tem sido associada ao impacto negativo na vida diária das pessoas 8,9 , ressaltando a necessidade do reconhecimento de grupos mais acometidos, além do diagnóstico e tratamento adequado, a fim de minimizar tais impactos.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…The results showed that in the inter-arch relation, Class I malocclusion prevailed over Class II and Class III, in agreement with the majority of the studies in the literature researched [12][13][14][15][17][18][19][20] . Some studies were observed to draw attention to the high number of molar relationships in Class I [12][13][14][15][17][18][19][20] , and on the other hand, authors 12,[21][22] emphasized the predominance of Class II, in comparison with relation Class I and Class III. This may be explained by the diversity of methodology used, and by the regional differences, age and sample size, or by the fact of considering normal occlusion as being Class I.…”
Section: Discussionmentioning
confidence: 99%